Determination of the bending strength of corner joints –metal corner brace, for corps furniture made of refined panel of of particleboards - Antovska, Ivana; Krstev, Marija; Jevtoska, Elena; Gruevski, Gjorgi (My University, 2021)
This paper presents data about the bending strength of outside corner joint – metal corner brace, for corps furniture made of refined panels of particleboard with a width of 25 mm. The research was conducted on two kinds of samples. The two kinds of sample objects are divided in two groups according to the way of composition as follows: group 1: the first are obtained by extraction i.e. cutting up an already constructed element – bedside table which was subjected to a test method for determining strength, durability and stability- furniture for indoor use EN 1730: 2000; group 2: the second sample objects were not subjected to any tests and were composed of two parts of particle board with given dimensions in accordance with the normative and are connected with the chosen connective object.